Gestión crediticia y su incidencia en la rentabilidad financiera de la Cooperativa de Ahorro y Crédito “Hermes Gaibor v” Ltda. del cantón Pangua, año 2017 - Morales Inguillay, Pedro Fernando (2018)
The present research project was carried out in the Savings and Credit Cooperative "Hermes Gaibor V." Cía. Ltda., Which is an institution dedicated to financial intermediation, the institution currently lacks good control, reporting and execution of credit management. Therefore, it has weaknesses in the application of tools both financially and administratively that allow controlling daily operations and credit management. The purpose of this research is to analyze the credit management of the establishment, facilitating the placement of credits and promoting the culture of savings among its members and thus allow the development of the cooperative, growth of its members, generating trust and organization within a framework of seriousness and solvency. The methods of deductive, descriptive, analytical, statistical and explanatory research were applied, which allow to determine the compliance of policies, to detail the elements of the object of study, to analyze the incidence of financial management, to determine the size of the sample, and to help to perform an analysis of the causes of a problem and its consequences. According to the main results obtained, it is evident that approximately 70% of the partners consider that the procedures for accessing a loan are complex and 91% of the members that have credit claim that they have fallen into default.